“Thinking of Britain” from Afar: Itineraries of British History as Centre and Periphery - Syriatou, Athena (Historein, 2025)
This article argues that in twentieth-century historiography trends have often placed – and sometimes misplaced – Britain at the centre or the periphery, depending on the historical context and the perspectives of historians themselves, who projected current preoccupations and cultural concerns onto the past. It thus emphasises the role of historiography in shaping perceptions of Britain’s place in the world, highlighting the interplay between centre and periphery and underscoring its prowess and power to still shape the world. Ultimately, it aims to explore the ways in which Britain both constructs and is constructed by the world, with a focus on several key publications that have become pivotal in British historiography.